2020
DOI: 10.36660/abc.20190231
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatina Reduz o Acúmulo de Células Musculares Lisas Vasculares para Inibir a Hiperplasia Intimal pela Inibição de Via p38 MAPK em um Modelo de Enxerto de Veia em Ratos

Abstract: Fundamento: A taxa de falha de enxerto de veia safena um ano após a cirurgia de revascularização do miocárdio varia de 10% a 25%. O objetivo deste estudo foi de investigar se a atorvastatina pode reduzir o acúmulo de células musculares lisas vasculares para inibir a hiperplasia intimal por meio da inibição da via p38 MAPK. Métodos: Quarenta e cinco ratos Sprague-Dawley foram randomizados em três grupos. Trinta ratos foram submetidos à cirurgia de enxerto de veia e randomizados para tratamento com veículo ou at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…p38MAPK signaling pathway is induced by stress stimuli and proinflammatory cytokines, and TNF-α is kind of a activator of p38 13 , 24 . Also, previous studies have shown a positive relationship between TNF-α and vein graft restenosis 16,25 . Thus, PTX may reduce the TNF-α expression to suppress the p38MAPK pathway for attenuation of restenosis.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…p38MAPK signaling pathway is induced by stress stimuli and proinflammatory cytokines, and TNF-α is kind of a activator of p38 13 , 24 . Also, previous studies have shown a positive relationship between TNF-α and vein graft restenosis 16,25 . Thus, PTX may reduce the TNF-α expression to suppress the p38MAPK pathway for attenuation of restenosis.…”
Section: Discussionmentioning
confidence: 84%
“…The details for experiments have been shown in previous studies [15][16][17] . Sprague Dawley (SD) rats (male, aged 10-12 weeks, body weight 275-325 g) were purchased from Anhui Lab Animal Research Center and were randomly assigned to sham group (sham operated without bypass), control group (bypass only), vehicle gel treatment group (bypass + pluronic-F127 gel), and PTX treatment groups (bypass + pluronic-F127 gel + PTX) (n = 10 per group).…”
Section: Methodsmentioning
confidence: 99%
“…Another substantial atorvastatin effect included the reduction of TNF-α and IL-6 levels into MS, suggesting that these cytokines modulate the endothelial remodeling process. 15 Therefore, the results of this study show that atorvastatin interventions may be effective as a medical intervention for preventive strategy and treatment of vascular conditions associated with MS. However, further studies are needed to elucidate potential mechanisms involved with metabolic and cardiovascular disorders in MS.…”
mentioning
confidence: 69%